RESISTANCE AND CRITIC AGAINST BOURGEOISIE IN WIDJI THUKUL’S POEM “BUNGA DAN TEMBOK” - Lesmana, Yogi Wijaya; Zahraniarni; Izfadlillah, Thesa (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
Understanding Indonesian poetry from the New Order Period offers important insights on the social, economic and political situation of that period.